GMAT Question of the Day - Daily to your Mailbox; hard ones only

It is currently 22 Oct 2019, 06:47

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

If x ≠ y, is x + y − xy = 0? (1) (1 − x)(1 − y) = 1 (2) (x + y)(x − y

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Find Similar Topics 
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 58428
If x ≠ y, is x + y − xy = 0? (1) (1 − x)(1 − y) = 1 (2) (x + y)(x − y  [#permalink]

Show Tags

New post 30 Oct 2018, 04:18
00:00
A
B
C
D
E

Difficulty:

  35% (medium)

Question Stats:

70% (01:32) correct 30% (02:22) wrong based on 48 sessions

HideShow timer Statistics

GMAT Club Legend
GMAT Club Legend
User avatar
V
Joined: 12 Sep 2015
Posts: 4017
Location: Canada
Re: If x ≠ y, is x + y − xy = 0? (1) (1 − x)(1 − y) = 1 (2) (x + y)(x − y  [#permalink]

Show Tags

New post 30 Oct 2018, 08:02
Top Contributor
Bunuel wrote:
If x ≠ y, is x + y − xy = 0?

(1) (1 − x)(1 − y) = 1
(2) (x + y)(x − y) = xy(x − y)


Given: x ≠ y

Target question: Is x + y − xy = 0?

Statement 1: (1 − x)(1 − y) = 1
Use FOIL to expand left side: 1 - y - x + xy = 1
Subtract 1 from both sides to get: -y - x + xy = 0
Multiply both sides by -1 to get: (-1)(-y - x + xy) = (-1)(0)
Simplify: y + x - xy = 0
PERFECT
The answer to the target question is YES, x + y − xy DOES equal 0
Since we can answer the target question with certainty, statement 1 is SUFFICIENT

Statement 2: (x + y)(x − y) = xy(x − y)
Since we're told x ≠ y, we know that (x - y) ≠ 0, which means we can safely divide both sides by (x -y)
When we do so, we get: x + y = xy
Subtract xy from both sides to get: x + y - xy = 0
PERFECT
The answer to the target question is YES, x + y − xy DOES equal 0
Since we can answer the target question with certainty, statement 2 is SUFFICIENT

Answer: D

Cheers,
Brent
_________________
Test confidently with gmatprepnow.com
Image
VP
VP
User avatar
D
Joined: 31 Oct 2013
Posts: 1465
Concentration: Accounting, Finance
GPA: 3.68
WE: Analyst (Accounting)
CAT Tests
Re: If x ≠ y, is x + y − xy = 0? (1) (1 − x)(1 − y) = 1 (2) (x + y)(x − y  [#permalink]

Show Tags

New post 31 Oct 2018, 03:17
Bunuel wrote:
If x ≠ y, is x + y − xy = 0?

(1) (1 − x)(1 − y) = 1
(2) (x + y)(x − y) = xy(x − y)



Given

x + y - xy = 0

x + y = xy

Statement 1:

(1 − x)(1 − y) = 1

1 - y -x + xy = 1

- y - x + xy =0

xy = x + y.

Sufficient.

Statement 2:

(x + y ) ( x - y ) = xy ( x - y)

x + y = xy

Sufficient .

The best answer is D.
GMAT Club Bot
Re: If x ≠ y, is x + y − xy = 0? (1) (1 − x)(1 − y) = 1 (2) (x + y)(x − y   [#permalink] 31 Oct 2018, 03:17
Display posts from previous: Sort by

If x ≠ y, is x + y − xy = 0? (1) (1 − x)(1 − y) = 1 (2) (x + y)(x − y

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  





Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne